GIVING OF DIFFERENT NATURAL FEED ON THE GROWTH AND SURVIVAL FISH OF LARVAE INGIR-INGIR (Mystus nigriceps) - Muhammad Yusuf; Sukendi '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in December 2015 to until February 2016 at Fish Hatchery and Breeding laboratory, Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this research was to determine the effect of the best natural feed on the growth and survival of larvae Ingir-ingir (M.nigriceps). This research used the experimental method, with completely randomized design (CRD) with 3 levels of treatment and 3 replications. The treatments in this research were P1 (Feeding naturally worms Tubifex sp.), P2 (natural feeding Kutu air), and P3 (natural feeding Artemia sp.).The result showed that feeding Tubifex sp. naturally on the best to feed the growth of absolute weight that produces 0.341 grams, the growth of the absolute length of 3.17 cm, the daily growth rate of 16.195%. While the best survival rate found in the natural feeding Tubifex sp. and Kutu air each 90 %.Keywords: Natural food, M. nigriceps, growth, and survival